Effects of heparin and enoxaparin on APP processing and Aβ production in primary cortical neurons from Tg2576 mice. - Hao Cui (Public Library of Science (PLoS), 2011)
Background Alzheimer's disease (AD) is caused by accumulation of Aβ, which is produced through sequential cleavage of β-amyloid precursor protein (APP) by the β-site APP cleaving enzyme (BACE1) and γ-secretase. Enoxaparin, a low molecular weight form of the glycosaminoglycan (GAG) heparin, has been reported to lower Aβ plaque deposition and improve cognitive function in AD transgenic mice. Methodology/principal findings We examined whether heparin and enoxaparin influence APP processing and inhibit Aβ production in primary cortical cell cultures. Heparin and enoxaparin were incubated with primary cortical cells derived from Tg2576 mice, and the level of APP and proteolytic products of APP (sAPPα, C99, C83 and Aβ) was measured by western blotting. Treatment of the cells with heparin or enoxaparin had no significant effect on the level of total APP. However, both GAGs decreased the level of C99 and C83, and inhibited sAPPα and Aβ secretion. Heparin also decreased the level of β-secretase (BACE1) and α-secretase (ADAM10). In contrast, heparin had no effect on the level of ADAM17. Conclusions/significance The data indicate that heparin and enoxaparin decrease APP processing via both α- and β-secretase pathways. The possibility that GAGs may be beneficial for the treatment of AD needs further study.